A note of wind engineering: Describing tower pre-assembly work at quayside for offshore wind turbine - Yusi Shih (Energy Reports, 2020)
A tower of an offshore wind turbine usually has several sections. The sections need to be assembled to form a full tower and be ready for nacelle installation. The assembly work can be performed at a designated sea site but it can be exposed in many risks. Instead, towers can be pre-assembled at quayside prior shipping to the sea site to reduce risks. In the present paper, the author shares the experience on tower pre-assembly work at quayside, in the wind engineering aspect. The wind engineering in this work includes wind data collection, wind data analysis, aeroelastic phonomoun of the towers, and eventually the aerodynamic loads on the towers. In the beginning, wind detector LiDAR is introduced to collect the wind data, and then the Method of Independent Storms is demonstrated for wind data analysis. For aeroelasticity, the present work showed that the vortex shedding frequency resonates with the natural frequency and the flutter frequency. Finally, through the gust factor and drag coefficient, aerodynamic load to the tower is determined, to be the result of the present work. The purpose of this work is to provide a complete approach to calculate the aerodynamic load on the tower, from the very beginning of wind data collection. All data and inputs in this paper are random, to avoid infringing intellectual properties and patents.
Keywords: 330; Offshore wind turbine; Risk; Tower pre-assembly; Wind engineering